The snake, the crocodile, and the dog eaudiobook - Peters, Elizabeth (Amelia Peabody, 1992)
Amelia hopes to rekindle some of the old fire with Emerson in a return journey to Amarna, Egypt where they met 13 years before. But her plan is foiled when Emerson emerges from a night-time ambush typically furious and with absolutely no memory of who Amelia is!